Diagnostyka gospodarki lokalnej - problem doboru i standaryzacji symptomów - Głuszczuk, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The term local economy diagnostics, as shown in the article, defines a method of cognition of reality and description of its state, but does not specify precisely the subject of research. That is because the term local economy is of conventional character. The conventional definition facilitates discussion on selection and standardization of symptoms. They are summarized by general principles governing selection of crucial diagnostic features, as well as assessment of their standardization ability with the use of analytic reference basis. Out of the presented multi variant solutions, discussions and critique, a conclusion emerges which is contained in one sentence: It is true that we cannot say if the image that we get (the state of local economy) precisely mirrors reality or if it is rather distorted, but it is better to have an imperfect image and be closer to the philosophical All I know is that I know nothing than to quit striving for unattainable perfection. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 244-252